An uncertain computational model for random vibration analysis of subsea pipelines subjected to spatially varying ground motions. (15th March 2019) - Zhang, Yahui; Li, Yuyin; Kennedy, David
Highlights: An uncertain model is presented for the random vibration of a subsea pipeline. The spatial variation of ground motions is considered. The unilateral contact relationship between the pipeline and seabed is considered. Propagations of the randomness and modelling uncertainties are investigated. Abstract: Based on a nonparametric modelling approach, this paper presents a random vibration analysis of a subsea pipeline subjected to spatially varying ground motions. The earthquake-induced ground motions are modelled as nonstationary random processes and their spatial variations are considered. The modelling uncertainties of the subsea pipeline are taken into account using a random matrix theory, while the unilateral contact relationship between the pipeline and seabed is also considered. Thus, an uncertain computational model for the subsea pipeline subjected to a random earthquake is established, and the corresponding solutions are calculated using Monte Carlo simulation (MCS). In order to highlight the contribution of the unilateral contact effect to random responses of pipelines, comparative studies are performed between the unilateral and permanent contact models. In numerical examples, the possible convergence problems in the present computational model are firstly studied to determine the optimal numbers of reduced modes and MCS samples. Then influences of the randomness in the earthquake and modelling uncertainties in the pipeline are investigated qualitatively through three representative cases. The different propagations of randomness and modelling uncertainties in the unilateral and permanent models are also examined and discussed. It is concluded that the randomness of the earthquake and modelling uncertainties of the pipeline have significant influences on the statistical characteristics of earthquake responses of the pipeline.